2021
DOI: 10.1101/2021.03.31.437859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Standing covariation between genomic and epigenomic patterns as source for natural selection in wild strawberry plants

Abstract: Adaptive evolution is generally thought to be the result of natural selection predominantly acting upon pre-existing DNA sequence polymorphisms through gene-environment interactions. Epigenetic inheritance is, however, recently considered an additional molecular force driving adaptive evolution independent of DNA sequence variation. Through comparative analyses of genome-wide genetic (SNPs) and epigenetic (DMCs) variation of wild strawberry plants raised under distinct drought settings, we demonstrate intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This is in agreement with previous studies which reported that mCHH was most dynamic in response to different climates [ 9 ]. More specifically, in the case of F. vesca , altitude variations of natural strawberry populations was found to be correlated with a high variability in DNA methylation in the CHH context [ 16 , 49 ]. In our study, cold stress, heat stress, and salt stress resulted in substantial local loss of DNA methylation in all sequence contexts, particularly in regions close to TSS and TES sites ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies which reported that mCHH was most dynamic in response to different climates [ 9 ]. More specifically, in the case of F. vesca , altitude variations of natural strawberry populations was found to be correlated with a high variability in DNA methylation in the CHH context [ 16 , 49 ]. In our study, cold stress, heat stress, and salt stress resulted in substantial local loss of DNA methylation in all sequence contexts, particularly in regions close to TSS and TES sites ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with studies which reported that mCHH was most dynamic in response to different climates (Dowen et al , 2012; Dubin et al , 2015; Kenchanmane et al , 2019). More specifically, in the case of F. vesca, altitude variations of natural strawberry populations was found to be correlated with a high variability in DNA methylation in the CHH context (De Kort et al , 2020; Kort et al , 2021). In our study, cold, heat, and salt stress resulted in substantial local loss of DNA methylation in all sequence contexts, particularly in regions close to TSS and TES sites in the F. vesca genome (Fig.…”
Section: Discussionmentioning
confidence: 94%